The role of the international community in the cause of the independence of peoples after the cold war A comparative study - االسخاذ امىساغد امدكخِر كىال غتداهلل خسي امجاف (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The will of the actors in the international community seeks to achieve their interests and the stability of their national security through their foreign policies and their cooperation at the international and regional levels on international issues. This endeavor may or may not coincide with the principles of international law and international conventions, Which witnessed the development of events since the beginning of the twentieth century. After the end of the Cold War, the will of the international community was able to address a number of issues of peoples' independence, as in the case of the people of Kosovo, but failed to reach suitable solutions to address the issue of the people of the Kurdistan Region of Iraq. The process of intervention by the international community in the internal conflicts after the Cold War has been a distinct case for the United Nations the face of these crises, but the difficulty of resolving some of them is related to the interests of the great powers and the interests of the parties to the crisis. The alternative to war is the agreement on political arrangements that accommodate the interests of all. The international community does not support the criterion of dividing countries to resolve internal conflicts, because the process of dividing countries between the conflicting parties is not a solution supported by most countries, because of maintaining their territorial integrity and ability The protection of its citizens, and may lead to an escalation of tension in society, so the operation within the State is considered the preferred option.